Main characteristics and anthropometrics of people with down syndrome – Impact in garment design - Barboza, Rochelne (2018)
Among the human chromosome abnormalities, Down Syndrome is the most prominent. Social perception challenges include prejudice, myth and exclusion, with social inclusion having been subject of several studies. From this perspective, the main objective of this study is to contribute to a higher social inclusion of people with Down Syndrome. This is addressed by an anthropometric characterization study of Down Syndrome individuals, performed with the technology of body scanning (3D Body Scanner). The presented study can support the development of inclusive clothing, adapted to people with special needs, promoting the anthropometric and ergonomic aspects of shape, comfort and aesthetics, which would lead to an increased quality of life, self-esteem and security, contributing to a higher inclusion in our society. The results from the data obtained through the measuring tables provided by the 3D Body Scanner System allow the identification of the main body shapes of the analyzed sample, as well as the main variables of their measurements. The impact characteristics from this specific population in the garment design process is also discussed.